Congressional Representation by Petition: Assessing the Voices of the Voteless in a Comprehensive New Database, 1789–1949. Issue 3 (6th September 2020) - Blackhawk, Maggie; Carpenter, Daniel; Resch, Tobias; Schneer, Benjamin
Abstract : For much of American political history, the electoral franchise was restricted to only a portion of the population. By contrast, the right to petition was considered universal and enshrined in the First Amendment, giving voice to the voteless. Petitioning thus served as a fundamental mechanism of representation. Still, fundamental questions remain: How was petitioning used, how did Congress respond to petitions, and did the petition allow for partial representation of the marginalized and unenfranchised? We address these questions by analyzing the Congressional Petitions Database (CPD), an original endeavor tracking virtually every petition introduced to Congress from 1789 to 1949. Our analyses document how (1) two important groups of unenfranchised constituents—Native Americans and women—petitioned regularly and (2) Congress's initial treatment of Natives' and women's petitions was similar to that of all others, thus offering systematic evidence highlighting the petition's role as a mechanism for representation among otherwise unenfranchised groups.